We Carry Their Bones : The Search for Justice at the Dozier School for Boys - Kimmerle, Erin H. (New York, NY : William Morrow, an imprint of HarperCollinsPublishers, 2022)
Recounts the story of the Dozier School, a Florida reform school shut down in 2011 due to reports of cruelty, abuse, and mysterious deaths, and the efforts of the author, a leading forensic anthropologist, to locate and exhume the graves of the boys buried there in order to reunite them with their families
Opening the earth -- New light -- Graveyard -- The Battle of Boot Hill -- "Satan has his seat" -- A meeting with the chief -- "Hell on Earth" -- "We can't forget... what happened in Jackson County" -- "Oftentimes, history doesn't include the good parts" -- "Thank you for all your good work" -- Reconstruction -- Identification -- "It's not even past" -- "Where is he?" -- "The unimaginable happened at Dozier" -- "You have the truth on your side" -- What remains
Includes bibliographical references (pages 223-230) and index
Text in English
Keywords: Kimmerle, Erin H; Florida School for Boys -- History; Reformatories -- Florida -- History; Imprisonment -- Florida -- History; Inmates of institutions -- Abuse of -- Florida -- History; Forensic anthropology -- Florida -- Case studies